Video display terminal use and other risk factors for abnormal blinking in children: gender differences. - Zhao, Hui; Wu, Shi-Nan; Zhang, Qi; Zhao, Chen; Shu, Hui-Ye; Ge, Qian-Min; Shao, Yi (BMC Ophthalmology, 2021)
Objective: To explore the risk factors for abnormal blinking in children and compare these between boys and girls.Methods: Children attending the Children's Optometry Clinic between June 2019 and June 2020 were recruited for the study. The time they had spent viewing video displays (VDTt) over the past 6 months was recorded. Incomplete blinking (IB) and blinking rate were measured and all participants were allocated to groups based on their blink rate (<20 times/min = normal blinking group, NBG; ≥20 times/min = abnormal blinking group, ABG). Tear film (TF) stability was also evaluated. The corresponding statistical methods are used to analyze the data.Results: A total of 87 boys and 80 girls were enrolled in the study. No significant difference in age was found between the 2 groups. There was a significant difference in TF stability between the two groups (P<0.05). According to binary logistic analysis, VDTt and ocular protection index (OPI) are important risk factors for abnormal blinking, with cut-off values of 1.75 hours and 1.014 respectively in boys; and 1.25 hours and 1.770 respectively in girls. The average of lipid layer thickness was an important protective factor for children using VDT for long periods, with a cut-off value of 58.5 nm in boys and 53.5nm in girls.Conclusion: Risk factors for abnormal blinking in both boys and girls include VDTt and OPI.